The effects of perceived and actual financial knowledge on regular personal savings: Case of Vietnam - Thi Anh Nhu Nguyen; Zoltán Rózsa; Jaroslav Belás; Ľudmila Belásová (Journal of International Studies)
The paper examines the factors, which affect decision-making on regular personal saving behaviour in the context of an emerging market in Vietnam. Focusing on financial literacy, the paper uses a combined measure of actual financial knowledge and a self-assessment of overall financial knowledge. The sample of the study consists of 240 commercial banks customers selected in 12 branches of four banks in Ho Chi Minh City. The questionnaire covers: (1) actual financial knowledge; (2) self-rating of financial knowledge; (3) financial risk tolerance; and (4) demographic characteristics of the respondents. The results of a logistic regression analysis show that perceived and actual financial literacy have separate effects on regular personal saving. Particularly, actual financial knowledge has a statistically significant positive relationship with regular personal saving with odds ratio higher than 6.5 times. However, perceived financial knowledge and financial risk tolerance factor are not statistically significant with regular personal saving. Finally, this paper offers evidence that the interaction variable, which is used to combine education level with their major study, has a statistically significant relationship with regular personal saving.